2014
DOI: 10.3390/molecules20010111
|View full text |Cite
|
Sign up to set email alerts
|

3β-O-Tigloylmelianol from Guarea kunthiana: A New Potential Agent to Control Rhipicephalus (Boophilus) microplus, a Cattle Tick of Veterinary Significance

Abstract: Chemical investigation of Guarea kunthiana fruits, guided by their effect on the reproductive cycle of engorged females of the cattle tick Rhipicephalus (Boophilus) microplus-a major economic problem to the livestock industry worldwide-led to isolation of 3β-O-tigloylmelianol, a new protolimonoid, from the bioactive hexane phase obtained by partitioning the crude ethanol extract. An adult immersion test was performed. The compound strongly inhibited egg-laying and hatchability (99.2% effectiveness at a 0.01% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…C. murale showed highest oviposition deterrence activity (81.88%) followed by D. stramonium (79.58%), A. indica (74.10%), P. harmala , (68.14%) and T. terrestris (48.96%). Inhibition of egg-laying and hatchability (99.2% effectiveness at a 0.01% concentration) due to compound extracted from Guarea kunthiana against cattle tick Rhipicephalus (Boophilus) microplus is reported by Miguita et al (2014). Lantana camara extract caused significant reduction in number of eggs of M. domestica as reported by Elkattan et al (2011).…”
Section: Discussionmentioning
confidence: 81%
“…C. murale showed highest oviposition deterrence activity (81.88%) followed by D. stramonium (79.58%), A. indica (74.10%), P. harmala , (68.14%) and T. terrestris (48.96%). Inhibition of egg-laying and hatchability (99.2% effectiveness at a 0.01% concentration) due to compound extracted from Guarea kunthiana against cattle tick Rhipicephalus (Boophilus) microplus is reported by Miguita et al (2014). Lantana camara extract caused significant reduction in number of eggs of M. domestica as reported by Elkattan et al (2011).…”
Section: Discussionmentioning
confidence: 81%
“…This phase was then subjected to column chromatography procedures and the resulting bioactive fraction (LC 50 = 15.20 mg/mL, Table II ), containing two principal components, was further separated, leading to the isolation and characterisation of the known protolimonoids melianodiol ( 1 , major compound) and meliantriol ( 2 ) ( Figure ). Their structures were established on the basis of 1 H and 13 C NMR spectroscopic techniques supported by mass spectra, as well as by comparison with previously reported data, and authentic samples ( Puripattanavong et al 2000 , Kurimoto et al 2014 , Miguita et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meliaceae, the family to which the genus Guarea belongs, is a rich source of secondary metabolites, including limonoids and protolimonoids ( Taylor 1984 , Tan & Luo 2011 ). In a previous investigation of G. kunthiana , we isolated 1 and 2 from the fruits, and di- and sesquiterpenes, poliprenol-12, and α- and d-tocopherols from the leaves ( Garcez et al 2004 , Miguita et al 2015) . The fruits also yielded the limonoids humilinolide E, 2-hydroxy-6-deoxyswietenine, swietenin acetate and methyl angolensate ( Miguita et al 2014) , none of which were found to be present in our G. kunthiana bioactive fraction from which melianodiol ( 1 ) was obtained, despite the fact that limonoids are known for their biological, and particularly insecticidal, properties ( Tan & Luo 2011) .…”
Section: Discussionmentioning
confidence: 99%
“…On its 13 . By comparison of its spectral data with those described in the literature, the structure of compound 3 is identified with that of Methyl angolensate compound isolated for the first time from the fruits of Guarea kunthiana and exhibiting numerous biological activities: antiappetant, insecticide, anti-tumor against human cells (liver, kidney) [41,42].…”
Section: Chemical Analysismentioning
confidence: 99%